Therapeutic dietetics in Polish spas in the second half of the 19th century (Perspektywa stołu, 2023)
In the second half of the 19th century, the Polish lands under the Austrian and Russian partitions witnessed a rapid development of spa culture. The inhabitants of these areas not only decided to go to recognized foreign resorts, but at the same time began to use “native” health resorts, many of which were experiencing their heyday. At the same time, a process of democratization of spa culture took place. In Polish health resorts, a number of different types of treatment procedures were used, which did not differ from those carried out in the most famous European resorts. Simultaneously with the treatments, various types of therapeutic diets began to be introduced. Initially, they did not differ much from the point of view of different diseases and ailments of patients. However, with the progress of spa treatment, its “scientific” and the development of dietetics in the last decades of the 19th century and the beginning of the 20th century, a number of specialized therapeutic diets appeared. In addition, in some health resorts, special diets adapted to the therapeutic profile and character of a given town were introduced. This was an attempt to attract patients and guests. In the text, based on sources of various provenance, I intend to show selected, most characteristic curative diets of the time. In addition, I try to trace whether spas put emphasis on advertising dietetics and good cuisine. The analyzes concern the so-called “national” health resorts, i.e. Galician and those located within the borders of the Kingdom of Poland and in Cieszyn Silesia.